HUBUNGAN PENDAPATAN ORANG TUA DENGAN HASIL BELAJAR SISWA MATA PELAJARAN PRAKTIK DI SMK NEGERI 1 SINTUK TOBOH GADANG PADANG PARIAMAN - Afriani, Rini; Yulastri, Asmar; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The background of this research is the problems related to the learning result which is stile in the low level in the practical activity in Jasa Boga subject in the second grade students of the SMK Negeri 1 Suntuk Toboh Gadang Kabupaten Padang Pariaman school year 2014/2015 totalling 50 poople. This research was done in descriptine quantitive way by using correlation method. The population of this research is the parents of 50 student at the second grade of SMK Negeri 1 Sintuk Toboh Gadang Kabupatan Padang Pariaman in the 2014/2015 school year. Based on the data analysis, the oncome of the parents is in the level, ≤ Rp. 1.500.000,00 in fact with a percentage of 40%, achivementof the student show that 66% student cannot pass the test but only 34% pass the test. The analysis shows that there is a positive correlation between the parents income and learning result of the second grade students of SMK Negeri 1 Sintuk Toboh Gadang Kabupaten Padang Pariaman. Keyword : The Level Of Income, Parents, Learning Outcomes.